PENERAPAN STRATEGI MANAJEMEN PEMASARAN DALAM MENINGKATKAN PELAYANAN KEPADA PELANGGAN - H. Abdul Rasul (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2017)
The competitive strategy in today's era sees competition as the best option to stay afloat in long-term business. If competition in the era of hypercompetition can not be achieved, then the company will get competition monopoly or even perfect competition. Perfect competition in reality never existed, because it caused a lack of profits in long-term business, but was less desired by consumers who increasingly wanted a business environment atmosphere that returned to the saving of natural resources. Multi-national strategy management is also highly human-oriented and its ability to read global aspects is increasingly open. This global openness of business provides opportunities for multinational businesses to develop more visibly in ASEAN countries, East Asia, Pacific countries, Australia, and so on. Therefore, the competition strategy in the hyperkompetition era must be immediately revised and repositioned to produce a form of competition that better understand the ethics of global environment. In particular, it is a competitive strategy in business to continually strive to improve business performance, because with the ups and downs experiences that have been suffered, these companies are still able to be researched and analyzed in more depth.